Given that the complex numbers x , y , z satisfy the equations: x + y + z x 3 + y 3 + z 3 x 5 + y 5 + z 5 = = = 5 − 1 9 − 2 3 5 ,
what is the value of x 7 + y 7 + z 7 ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let X 3 + T X 2 + U X + V = 0 be the cubic equation that has roots x , y , z , then
By Vieta's formula, T = − 5
Apply the algebraic identity
x 3 + y 3 + z 3 − 3 x y z − 1 9 + 3 V V = = = = ( x + y + z ) ( x 2 + y 2 + z 2 − x y − x z − y z ) ( x + y + z ) ( ( x + y + z ) 2 − 3 ( x y + x z + y z ) ) 5 ( 5 2 − 3 U ) − 5 U + 4 8
Consider expanding the following expression
( x 2 + y 2 + z 2 ) ( x 3 + y 3 + z 3 ) ( 2 5 − 2 U ) ( − 1 9 ) ( 2 5 − 2 U ) ( − 1 9 ) + 2 3 5 3 8 U − 2 4 0 = = = = = = = = ( x 5 + y 5 + z 5 ) + ( x y ) 2 ( x + y ) + ( x z ) 2 ( x + z ) + ( y z ) 2 ( y + z ) − 2 3 5 + ( x y ) 2 ( 5 − z ) + ( x z ) 2 ( 5 − y ) + ( y z ) 2 ( 5 − x ) 5 ( ( x y ) 2 + ( x z ) 2 + ( y z ) 2 ) − x y z ( x y + x z + y z ) 5 ( ( x y + x z + y z ) 2 − 2 x y z ( x + y + z ) ) − x y z ( x y + x z + y z ) 5 ( U 2 − 2 ( − V ) ( 5 ) ) − ( − V ) ( U ) 5 U 2 + 5 0 V + U V 5 U 2 + V ( 5 0 + U ) 5 U 2 + ( − 5 U + 4 8 ) ( U + 5 0 )
Solve for U and V simultaneously gives U = 1 1 , V = − 7 . Thus the equation X 3 − 5 X 2 + 1 1 X − 7 = 0 has roots x , y , z . By rational root theorem, ( X − 1 ) is a root of the equation. Factorize it gives ( X − 1 ) ( X 2 − 4 X + 7 ) = 0 . Quadratic formula gives the other two roots 2 ± i 3
Hence, the answer is 1 7 + ( 2 + i 3 ) 7 + ( 2 − i 3 ) 7 = 5 0 9
I used modified Newton's sums, but your strategy works just as well (it's really the same thing, just in disguise).
Log in to reply
Same here.
Problem Loading...
Note Loading...
Set Loading...
If we let S n = x n + y n + z n and suppose that S 2 = a , we have S 0 = 3 , S 1 = 5 , S 2 = a , S 3 = − 1 9 and S 5 = − 2 3 5 . Playing with elementary symmetric polynomials (expressing x + y + z , x y + x z + y z and x y z in terms of S 1 , S 2 and S 3 ) tells us that x , y , z are the roots of the cubic X 3 − 5 X 2 + 2 1 ( 2 5 − a ) X − 2 1 ( 2 9 − 5 a ) = 0 and hence S n + 3 − 5 S n + 2 + 2 1 ( 2 5 − a ) S n + 1 − 2 1 ( 2 9 − 5 a ) S n = 0 for any integer n . Then S 4 = 2 1 ( a 2 − 5 0 a − 4 5 ) and the equation S 5 − 5 S 4 + 2 1 ( 2 5 − a ) S 3 − 2 1 ( 2 9 − 5 a ) S 2 = 0 collapses to a linear equation for a , which can be solved to obtain a = 3 . We now easily calculate S 6 = − 2 8 5 and S 7 = 5 0 9 .